The development of management guidelines for sustainable livestock farming in the Hawke's Bay : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Farm Management at Massey University - Collins, Heather Mildred (Massey University, 1996)
Regardless of how sustainable land management is defined, it will never be achieved unless land users are involved in, and committed to, its attainment. To commit to a goal of sustainability, stakeholders must share in the identification of resource management problems and in the development of solutions that are both economically and socially acceptable. Facilitated workshops were held with twelve farmer and two agribusiness groups in the Hawke's Bay during July and August 1994. The workshops were held to involve participants in the development of guidelines for pastoral farming in Hawke's Bay and Wairoa, using the "by farmers for farmers" approach. The farmer workshops were used to develop an operational description of sustainable livestock farming and to identify the main components of sustainability. The agribusiness workshops sought to encourage support by this sector for the guidelines and the farmers who would implement them. The advantages associated with sustainable farming applied to all components of the system. The farmer and family, natural resources (the farm), the community and future generations all were all seen to benefit from sustainable farming. Through the workshops, the farmers identified the components and criteria that describe sustainable farming. They suggested that sustainable farming may be recognised by practices that result in productive soil, sufficient water quantity, good water quality, productive pasture, appropriate trees, productive animals, and successful, prosperous and flexible farmers. Using the concept pyramid process, farmers identified key management practices that would result in the sustainable use of soil, water, animals and plants in the fanning system. A farming committee was elected to represent the views of farmers, and work with the consultant commissioned by Hawke's Bay Federated Farmers, to produce the pastoral farming guidelines. The management practices identified by farmers were written to a set of guidelines, which were circulated for public comment and submission. The workshop participants, stakeholders and the general public were involved in the consultation process, to continue the participatory approach utilised in the workshops. All workshop participants were sent a complimentary copy of the pastoral guidelines and a questionnaire. The survey aimed to assess the participants' perceptions and usage of the guidelines, as well as gauge farmer interest and obtain direction for follow-up work. In broad terms, the guidelines met the expectations of farmers and were viewed as being useful for encouraging discussion about, and implementation of, sustainable farming practices
Appendix 4 has been removed as it is copyrighted to Hawke's Bay and Wairoa Federated Farmers, but it may be consulted in the print copy in the Library.
Keywords: Farm management; New Zealand Wairoa County; 300202 Agricultural land management